1995
DOI: 10.1182/blood.v85.10.2756.bloodjournal85102756
|View full text |Cite
|
Sign up to set email alerts
|

Protein C deficiency in a controlled series of unselected outpatients: an infrequent but clear risk factor for venous thrombosis (Leiden Thrombophilia Study) [see comments]

Abstract: A deficiency of protein C (PC), antithrombin, or protein S is strongly associated with deep-vein thrombosis in selected patients and their families. However, the strength of the association with venous thrombosis in the general population is unknown. This study was a population-based, patient-control study of 474 consecutive outpatients, aged less than 70 years, with a first, objectively diagnosed, episode of venous thrombosis and without an underlying malignant disease, and 474 healthy controls who matched fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
177
4
11

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(201 citation statements)
references
References 28 publications
8
177
4
11
Order By: Relevance
“…Family members with protein C deficiency have an 8-1 0-fold increased risk of venous thrombosis and by the age of 40. half of them will have experienced at least one thrombotic event [ 16,1 7]. This risk is similar to that observed in a population based study [10].…”
Section: Protein C Deficiencysupporting
confidence: 77%
See 2 more Smart Citations
“…Family members with protein C deficiency have an 8-1 0-fold increased risk of venous thrombosis and by the age of 40. half of them will have experienced at least one thrombotic event [ 16,1 7]. This risk is similar to that observed in a population based study [10].…”
Section: Protein C Deficiencysupporting
confidence: 77%
“…In a population-based control study the relative risk for APC resistance was 7 whereas for protein C deficiency it was 6. 5 suggesting that the two abnormalities do not differ in severity [10,26].…”
Section: Apc Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Our study demonstrated the FV : R506Q mutation to be an important risk factor in outpatients with DVT. This is in marked contrast to other congenital prothrombotic disorders, which are only rarely found in thrombosis patients [19][20][21][22][23][24]. More than a quarter of the outpatients with venous thrombosis verified by phlebography were found to be carriers of the FV : R506Q mutation, a strikingly high proportion, even larger than figures reported for selected series of thrombosis patients from other countries [2,4,9,12].…”
Section: Discussionmentioning
confidence: 60%
“…In the general population, a low level of circulating protein C as well as common variants in the protein C gene is associated with increased risk of venous thromboembolism [Folsom et al, Supporting Information is available in the online issue at wileyonlinelibrary.com. * Correspondence to: Weihong Tang Koster et al, 1995;Smith et al, 2007]. Activated protein C has other physiologic effects including anti-inflammatory and antiapoptotic activities and endothelial barrier stabilization [Jackson and Xue, 2008].…”
Section: Introductionmentioning
confidence: 99%